Orally dosing steers with Lactipro (Megasphaera elsdenii) decreases the quantity of roughages fed during finishing - Miller, K.A.; Van Bibber-Krueger, C.L.; Drouillard, James S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2013)
The cost of roughages is relatively high in comparison to their contribution of nutrients to feedlot diets. Widespread drought has affected roughage supplies in the cattle-feeding regions of the United States, further increasing the cost of roughages for feedlots. Despite their relatively high cost, roughages are incorporated into finishing diets to maintain rumen function and to manage ruminal acidosis. The greatest proportion of roughage is utilized early in the feeding period when cattle are being transitioned from forage-based diets to concentrate-based diets, allowing ruminal microbes to adapt gradually to higher levels of starch and sugars. If cattle are not properly adapted to concentrate-based diets, undesirable lactic acid-producing microorganisms, such as Streptococcus bovis, can rapidly proliferate and produce large excesses of lactic acid in the rumen. This condition can precipitate feedlot acidosis, which can have serious consequences for health and performance of cattle. Lactipro (MS Biotec, Wamego, KS) is a probiotic drench containing Megasphaera elsdenii, which is a lactate-utilizing bacterium that prevents lactic acid accumulations in the rumen of grain-fed cattle. Lactipro has been used successfully to accelerate the adaptation of cattle from roughage-based diets to concentrate-based diets. The objective of this study was to determine if Lactipro could be utilized to eliminate the step-up period for feedlot cattle, and in so doing decrease the amount of roughage required during the finishing period.
Keywords: Cattle; Lactipro; Roughages; Steer performance; Carcass characteristics